Surgical outcomes in eastern Uganda: a one-year cohort study. (3rd September 2018) - Hewitt-Smith, A; Bulamba, F; Olupot, C; Musana, F; Ochieng, JP; Lipnick, MS; Pearse, RM
Abstract : Introduction: There is urgent need to improve access to safe surgical treatments for patients in low- and middle-income countries (LMICs). However, few data exist to characterise clinical outcomes for this patient population. Methods: Consecutive patients undergoing surgery at a referral hospital in Uganda were prospectively followed between October 2016 and October 2017. The primary outcome was in-hospital, postoperative mortality. Secondary outcomes were in-hospital complications for patients undergoing laparotomy and Caesarean section. Results are presented as n (%) or odds ratios (OR) with 95% confidence intervals. Results: A total of 4 773 patients of mean age 28 years were included; 3 754 were female (79.0%) and 4 259 patients (89.4%) were classified as American Society of Anesthesiologists class I or II. Some 3 501 (73.8%) procedures were performed on an emergency basis. The most frequent procedure was Caesarean section (2 634 patients [55.3%]). There were 93 deaths (2.0%), 49 of which occurred after the day of surgery (59.0%). In multivariable analysis, patients undergoing general (abdominal) surgery were at greatest risk of death (OR 4.34 [2.02–9.30]). Postoperative complications were recorded for 24/412 (5.8%) patients undergoing Caesarean section and 18/107 (16.8%) patients undergoing emergency laparotomy. Infection was the most frequent complication in these patient groups (33/519 patients [6.4%]). Conclusions : This study confirms the feasibility of longitudinal audit of postoperative outcomes in LMICs. Data collected over a one-year period were highly consistent with the findings of a recent seven-day cohort study conducted across Africa.